Ethics from an Islamic Perspective - Abdullahi Hassan Zaroug (International Institute of Islamic Thought, 1999)
The purpose of this article is to show the complexity of the field of ethics and to point to the need for a comprehensive study in the discipline of Islamic ethics. It makes a preliminary attempt at tackling foundational issues on the subject, such as the possibility of morality; its importance. autonomy, nature, and scope; and the possibility of historical studies. It also reviews some contemporary works on Islamic ethics, especially the methods they used to study Islamic ethics, in order to show their points of strength and vulnembility. Finally, it gives a brief account of the contributions of the different Muslim schools of thought to ethics and recommends cerrain topics for further study.